Prevalence and Clinical Significance of Streptococcus dysgalactiae subspecies equisimilis (Groups C or G Streptococci) Colonization in Pregnant Women: A Retrospective Cohort Study. (3rd June 2018) - Jaalama, M.; Palomäki, O.; Vuento, R.; Jokinen, A.; Uotila, J.
Abstract : Objectives. Little is known about the significance of Streptococcus G or C colonization in pregnant women. The objective of this study was to assess whether vaginal Streptococcus group G or C colonization detected in late pregnancy increases the infectious morbidity of the mother or newborn. Methods . A total of 15, 114 rectovaginal cultures taken at 35–37 weeks of pregnancy were analyzed at Tampere University Hospital, Finland, between 2012 and 2014. From this laboratory data, all Streptococcus G or C-positive cultures were included to study maternal and neonatal infectious morbidity after delivery. This study population was compared to women with a positive Streptococcus B culture and to women with a negative culture. Results . The prevalence of Streptococcus G or C colonization was 2.9%. Significantly more postpartum endometritis was found in this study group. No association was found between colonization and neonatal bacteremia. Conclusions . Streptococcus G or C colonization is associated with postpartum endometritis. More research is needed to clarify if antibiotic prophylaxis is reasonable for this group during delivery.